IMPROVING READING COMPREHENSION OF THE EIGHTH-GRADE STUDENTS OF SMPN 4 DENPASAR THROUGH KWL PLUS - Ni Komang Aninda Cahyaning Rahayu Suwarsiki; Ni Luh Putu Dian Sawitri; Ni Wayan Krismayani (Academic Journal on English Studies (AJOES), 2023)
Reading comprehension is a crucial skill that enables individuals to acquire new information. This study at SMPN 4 Denpasar aimed to enhance the reading comprehension of class VIII.10 students. Using the Classroom Action Research method over two cycles, the initial pre-test mean score was 63.00, with only 35% students who could passed. Cycle I, employed the KWL Plus strategy, showed a post-test I mean score of 85.25, and 82.5% of the students who could passed. In Cycle II, with the same strategy, post-test II mean score was 97.25, and 97.5% of the students who could passed. A concluding questionnaire showed 35.22% strongly agreed, 52.72% agreed, and 12.04% were undecided. The study highlights the effective enhancement of reading comprehension of the eighth-grade students of SMPN 4 Denpasar in the class VIII.10, affirming the success of the KWL Plus strategy in the academic year 2023/2024.